DEVELOPMENT OF A THINKING SKILL TEACHING MODEL IN DISAIN PEMBELAJARAN SUBJECT - Susi Herawati; Najmiatul Fajar (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
The thinking skill teaching model which is based on metacognitive theory is a teaching method that requires students' skills in managing and controlling themselves to develop their thinking ability. The developed thinking skill model refers to four types of skills, namely problem-solving skills, decision-making skills, critical and creative thinking skills. The teaching model is developed to teach students’ thinking ability. This is a research and development study that adopts Borg & Gall (1989) steps consisting of four stages, namely (1) Collecting information (including literature review, observation of existing tools and creating research framework); (2) Designing (formulating research objectives, estimating funds and time required and research work procedures); (3) Developing initial product form (initial draft of product design); and (4) conducting initial field trials. Based on the result of the research, it is found that 1) the developed thinking skill model is the research that tries to develop a learning model to develop and improve students' thinking ability, 2) the theoretical foundation of the development of this thinking skill model is metacognitive theory, 3) the product validation result generated, in the form of modules and assessment instruments, is in valid category, because the products produced is in line with the theoretical basis used, 4) based on the practicality of the product, in the form of modules and valuation instruments, it was found that it is in the practical category, meaning that the resulted product is applicable in teaching students’ thinking capability.